Numerical modeling and parallel computations of heat and mass transfer during polymer flooding of non-uniform oil reservoir developing by system of producing and injecting wells - Konyukhov, V M; Konyukhov, I V; Chekalin, A N (Journal of physics. Conference series, 2019)
The mathematical and numerical models are developed for computation of interrelated thermal and hydrodynamic processes in the unified oil-producing complex during the polymer flooding of the heterogeneous oil reservoir exploited with a system of arbitrarily located injecting wells and producing wells equipped with submersible multistage electric centrifugal pumps with regulation of their working modes by the surface control stations. The complete differential model includes equations governing non-stationary two-phase three-component filtration in the reservoir and quasi-stationary heat and mass transfer in the wells and working channels of pumps. Special non-linear boundary conditions and dependences simulate the influence of the drossel diameter and the frequency electric current, respectively, on the flow rate and pressure at the wellhead of each producing well and the performance characteristics of all submersible units. The oil field development is also regulated by changes in bottom-hole pressure of each injection well, the concentration of polymer in water solution, its total volume and duration of injection. The problem is numerically solved with the use of the finite difference method and the iterative algorithms with application of technologies of parallel computing. It is shown that parallelization can improve the performance of calculations at several times in comparison with sequential computing.